Effects of an experimental in situ seabed disturbance on deep-sea benthic ecosystem function and macro-infaunal community structure on the Chatham Rise, Southwest Pacific - Rachel Hale (PANGAEA, 2025)
We examined changes in environmental parameters following an experimental benthic disturbance using a modified plough (estimated 15 cm penetration) on the Chatham Rise (~450 m depth), Aotearoa/New Zealand. Sediment core retrievals were undertaken using an Oceans Instruments MC-800 multicorer fitted with six 70 cm long polycarbonate core tubes with 9.52 cm internal diameter that took place pre-disturbance on 16-17 June 2019 (voyage TAN1903), post-disturbance on 24-25 June 2019 (TAN1903) and one-year post-disturbance on 14-19 June 2020 (TAN2005). In order to determine any background changes in the larger surrounding area between years (2019, 2020), an additional reference site with similar hydrographic and sediment attributes (REF, depth = 455 m), located approximately 15 km to the north-west of the Butterknife (Figure 1B), was also sampled in the pre-disturbance period (n = 2, TAN1903) and one-year post-disturbance (n = 3, TAN2005). Measurements included sediment community oxygen consumption (SCOC), background nutrient (NH4, NOx, DRP) concentrations, nutrient fluxes, macro-infauna community composition (abundance, biomass, richness, diversity), sediment grain size (mean particle size, mud content, particle sorting, grain size skewness, grain size kurtosis), sediment chlorophyll a and phaeopigment content, sediment water content (H20), sediment total organic matter (TOM) content, and sediment particulate organic carbon (POC) and nitrogen (PN) content.